2012
DOI: 10.1007/s00595-012-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and time of recurrence after complete resection of esophageal cancer

Abstract: These findings reinforce the importance of careful follow-up for both loco-regional and hematogenous recurrence after esophagectomy, particularly during the first 2 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
62
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 22 publications
11
62
0
Order By: Relevance
“…after curative esophagectomy, followed by distant organ recurrence [3,9,10]. These studies have also demonstrated that distant organ recurrence had a poorer prognosis than loco-regional recurrence.…”
Section: Introductionmentioning
confidence: 94%
“…after curative esophagectomy, followed by distant organ recurrence [3,9,10]. These studies have also demonstrated that distant organ recurrence had a poorer prognosis than loco-regional recurrence.…”
Section: Introductionmentioning
confidence: 94%
“…In order to find out the failure pattern after surgery, several retrospective studies had been investigated and advices were A retrospective study of pattern of recurrence after radical surgery for thoracic esophageal carcinoma with or without postoperative radiotherapy concluded for clinic target delineation (22)(23)(24)(25). However, these researches were focused on the patients without PRT.…”
Section: Introductionmentioning
confidence: 99%
“…Lou et al (15) in a recently published study found that 54% of recurrences were detected in the first year of follow-up and 75% in the second year. Other series published at international level (4,10,16) concur in concluding that the majority of recurrences are detected during the first 2 years of follow-up.…”
Section: Discussionmentioning
confidence: 68%
“…Surgery involving oesophagectomy is still the main therapeutic option (2,3), although even after receiving curative treatment the possibility of recurrence in patients, either locoregional or distant, is still high, with percentages varying between 29% and 59% (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%